The impact of maize-bean intercropping on insect biodiversity - Hüber, Conny; Zettl, Freya; Hartung, Jens; Müller-Lindenlauf, Maria (Basic and applied ecology, 2022)
Intensive agriculture is one of the main reasons for recent insect declines. This loss of biodiversity has created the need to develop methods of intensive cultivation that combine high yields with biodiversity conservation. One promising method in maize cultivation is intercropping with beans. The objective of this study was to determine whether maize-bean intercropping could increase insect biodiversity. We examined the activity density, species richness and Shannon diversity of bees and carabid beetles in pure and intercropped maize under both organic and conventional management. We collected carabid beetles using pitfall traps and bees by doing transect walks. The study was carried out in an agricultural landscape, on a set of 17 study sites. We found that intercropping leads to significant increases in bumblebee and honeybee activity as well as in bee species richness. Differences between pure and intercropped maize were dependent on the year of data acquisition and the management style. Solitary wild bee species activity was not significantly affected. Carabid activity density and carabid species richness also did not differ significantly between the cropping systems. We conclude that maize-bean intercropping can contribute to insect biodiversity conservation but its contribution is limited to bumblebees. Despite its relatively low contribution per hectare, maize-bean intercropping could have a surprisingly positive impact, as maize now covers large areas of German farmland. Potential exists to increase the biodiversity value of maize intercropping even further by using varied plant mixes. Our results strongly encourage further research in this direction.